Performance Comparison of Hybrid Storage on OLAP Database Server Virtualization - Nirwansyah, Ferdy (Al Makki Publisher, 2024)
In today's digital era, efficient database management is important for companies to support analysis and decision-making processes. The use of On Line Analytical Processing (OLAP) in databases requires optimal storage configuration, especially in virtualization environments. This study aims to evaluate the performance of OLAP databases using hybrid storage configurations, combining Solid State Drives (SSD) and Hard Disk Drives (HDD), and identify the best configuration to improve database performance. The research method was carried out using the TPC-H benchmark on four database systems: Oracle, SQL Server, MySQL, and PostgreSQL. Four storage configurations were tested by allocating SSD for database storage and HDD for the operating system and temporary files, measured with 10 and 100 virtual users. The results showed that SQL Server provided the best performance in all configurations, with faster query execution times than other databases. The configuration with SSD for database storage and HDD for the operating system and temporary files proved to be the most efficient in reducing query latency. The conclusion of this study emphasizes the importance of using hybrid storage configurations in improving OLAP database performance in virtualization environments. Configuring with SSD as database storage and HDD for operating system and temporary files is the best choice to achieve high query performance.